The Effect Of Electronic Commerce And Brand Awareness On Purchasing Decisions At Shopee Online Shopping - Rohfik Adika; Subandrio Subandrio (BIMA Journal (Business, Management, & Accounting Journal), 2021)
The impact of the dynamics of business competition in the development of the world of information technology is getting more advanced and rapid from time to time so that purchases via virtual are increasing. The purposee off thiss study was to know the effect off electronic commercee and brand awareness on purchasing decision non Online shopee shopping (Case study on online shopping consumers of muhammadiyah university of bengkulu students).This research uses survey research method with quantitative data analysis. The population in this study were students of the University of Muhammadiyah Bengkulu who shop online at shopee with a total of 140 people, anddtheesample was taken usinggpurposiveesamplinggmethod. based on the resultssoffmultipleelinearr regression, it issobtained theeregressionnequationnY = 2.621 + 0.060 (X1) + 0.540 (X2).The resultssoffthe research and hypotheses show that electronic commerce (X1) is t-hitt-table (3.328 1.9774) and (sig α = 0.001 0.050), brand awareness (X2) is t-hitt-table (7,418 1.9774) and (sig α = 0.000 0.050)  simultaneously haveea significantteffectton purchasing decisions. Partially the two variables of electronic commerce and brand awareness have a significant effect on purchasing decisions.